DESENVOLVIMENTO, AVALIAÇÃO DO PERFIL DE SEGURANÇA E EFICÁCIA DE SISTEMAS NANOESTRUTURADOS CONTENDO ÓLEO ESSENCIAL DE LAVANDA NA NEUROPROTEÇÃO - Nedel, Sheila Spohr (2021)
With the increase in life expectancy and growth in the number of elderly people in the world, it is estimated that there is a high prevalence of neurodegenerative diseases, especially Alzheimer's disease. Treatment for this population can be through the use of drugs or non-pharmacological therapy. The effects of drugs are limited to delaying or halting the evolution of the disease, allowing only a temporary improvement in the patient. In relation to non-pharmacological therapy, aromatherapy stands out, which is part of phytotherapy and uses essential oils as therapeutics, but its disadvantage is high volatilization. As a way to protect its active compounds and ensure the effectiveness of these oils, the association of memos with nanotechnology stands out, which due to its size and characteristics can increase the mechanisms of cellular absorption, as well as its effectiveness. Thus, the aim of this study was to evaluate the feasibility of associating essential oils from two species of lavender in nanotechnology-based formulations and verify their safety profile, as well as their efficacy in an in vivo model of neuroprotection. This is an experimental study, where nanoemulsions containing L. angustifolia essential oil (NELA) and nanoemulsions containing L. dentata essential oil (NELD) were prepared and characterized, followed by their incorporation in hydrogels, as well as physical characterization -chemistry and stability evaluation. Afterwards, the safety and efficacy of the formulations was evaluated using the C. elegans model (CL2006). The results showed that liquid and semi-solid nanoformulations demonstrated adequate nanometric properties. The major components present in the essential oils, of each lavender species, were preserved in the nanoformulations, during the stability study at the refrigeration temperature. In the in vivo analysis we concluded that the doses of 0.1 and 2.5% of the nanoformulations did not change the survival rate of C. elegans after 1 hour of treatment, in addition, the treatment with 0.1% of both essential oils free did not alter the survival rate of C. elegans. In contrast, doses of 2.5 and 10% of both free L. angustifolia and L. dentata essential oils decreased the survival rate of C. elegans compared to the control group. When comparing the effectiveness of 0.1% and 2.5% nanoformulations, we observed that the responses for all formulations were better at the dose of 0.1% and that the nanoformulation that showed better responses in relation to paralysis was the one with GNELD, that is, with the essential oil of L. dentata. Thus, we can conclude that nanoformulations containing L. angustifolia and L. dentata essential oil at a concentration of 0.1% were safe and effective in a C. elegans model (CL2006).